Oxygen-dependent regulation of c-di-GMP synthesis by SadC controls alginate production in Pseudomonas aeruginosa - Schmidt, Annika Mareike; Hammerbacher, Anna Silke; Bastian, Mike; Nieken, Karen Jule; Klockgether, Jens; Merighi, Massimo; Lapouge, Karine; Poschgan, Claudia; Kölle, Julia; Acharya, K. Ravi; Ulrich, Martina; Tümmler, Burkhard; et al. (Environmental microbiology, 2016)
Pseudomonas aeruginosa produces increased levels of alginate in response to oxygen-deprived conditions. The regulatory pathway(s) that links oxygen limitation to increased synthesis of alginate has remained elusive. In the present study, using immunofluorescence microscopy, we show that anaerobiosis-induced alginate production by planktonic PAO1 requires the diguanylate cyclase (DGC) SadC, previously identified as a regulator of surface-associated lifestyles. Furthermore, we found that the gene products of PA4330 and PA4331, located in a predicted operon with sadC, have a major impact on alginate production: deletion of PA4330 (odaA, for oxygen-dependent alginate synthesis activator) caused an alginate production defect under anaerobic conditions, whereas a PA4331 (odaI, for oxygen-dependent alginate synthesis inhibitor) deletion mutant produced alginate also in the presence of oxygen, which would normally inhibit alginate synthesis. Based on their sequence, OdaA and OdaI have predicted hydratase and dioxygenase reductase activities, respectively. Enzymatic assays using purified protein showed that unlike OdaA, which did not significantly affect DGC activity of SadC, OdaI inhibited c-di-GMP production by SadC. Our data indicate that SadC, OdaA and OdaI are components of a novel response pathway of P. aeruginosa that regulates alginate synthesis in an oxygen-dependent manner.
Gesehen am 19.05.2020